(untitled) (Research, Society and Development, 2023)
During the gestational period, the woman advocates attention to her health and that of her fetus. In this phase, several hormonal changes occur that may predispose to diseases. Considering the relevance of preventive oral care in order to inhibit negative consequences for maternal and child health, this work will discuss the main literary findings about the importance of the dentist during prenatal care. For the construction of this research, it was necessary to identify the main theme and select the guiding question and, thus, the criteria for inclusion and exclusion of the studies were established. As an inclusion criterion, we opted for articles published within the period of 10 years and made available in English and Portuguese. The appointment with the dentist should be from the beginning of prenatal care. The individuality of each pregnant woman must be taken into account and her needs must be met, with regular consultations. Although the second trimester is the most indicated period for carrying out dental procedures, clinical care can be provided at any stage of pregnancy. The interaction between the dental surgeon and other health professionals is fundamental, so that the care takes place in a multidisciplinary and interdisciplinary way throughout the gestational period, in order to prioritize the health of the child and the mother.